BUKU SUPLEMEN KOMPETISI SAINS MADRASAH BIDANG GEOGRAFI TERINTEGRASI AGAMA - Digitalis, Gatra Orbita; Sumarmi, Sumarmi; Bachri, Syamsul; Mkumbachi, Ramadani Lausi (Universitas Negeri Malang, 2024)
SUPPLEMENTARY BOOK FOR MADRASAH SCIENCE COMPETITION IN GEOGRAPHY INTEGRATED WITH RELIGION This research aims to develop a supplementary book for the madrasah science competition in geography, integrated with Islamic teachings, focusing on geomorphology and land use. The book's feasibility was assessed based on criteria of validity, practicality, attractiveness, and effectiveness. The ADDIE model was utilized for product development. The feasibility assessment involved one material expert, one product expert, one practitioner, and ten students from the Olympic geography class. Product trials were conducted at MAN 2 Malang City. Data results indicate that the developed product is valid in terms of material content, very valid in product design, highly practical, highly attractive, and highly effective, making it suitable for use. Penelitian ini bertujuan untuk mengembangkan buku suplemen untuk kompetisi sains madrasah bidang geografi yang terintegrasi dengan ajaran Islam dengan fokus pada geomorfologi dan penggunaan lahan. Kelayakan buku dinilai berdasarkan kriteria validitas, kepraktisan, kemenarikan, dan keefektifan. Model ADDIE digunakan untuk pengembangan produk. Penilaian kelayakan melibatkan satu orang ahli materi, satu orang ahli produk, satu orang praktisi, dan sepuluh orang siswa dari kelas olimpiade geografi. Uji coba produk dilakukan di MAN 2 Kota Malang. Hasil data menunjukkan bahwa produk yang dikembangkan valid dari segi isi materi, sangat valid dalam desain produk, sangat praktis, sangat menarik, dan sangat efektif, sehingga layak untuk digunakan.